PENGEMBANGAN HANDOUT DENGAN TAMPILAN MAJALAH PADA MATERI SISTEM PERNAPASAN MANUSIA UNTUK SISWA SMP - Suwarti, Suwarti; Ardi, Ardi; Amri, Erismar (Pendidikan Biologi, 2013)
ABSTRACT  This research is base on observation in the SMPN 8 Solok Selatan. Teaching materials such as handout has never been used at this school. The teacher used teaching materials such as textbooks and student activity sheets (LKS) to support the learning process . But they were less attractive, especially in the human respiratory system material. The teaching material pictures were not complete and colorless. Thus necessary to develop a handout with appear of the magazine. Aims the research to know validity and practicalities handout with appear of the magazine on the human respiratory system material . This research was a development with 4D procedural model, which was done in STKIP PGRI Sumatera barat  and SMPN 8 Solok Selatan class VIII semester 1 of academic year 2012/2013. The study subjects were 6 validators, and to test the practicalities done by 3 teachers and 21 students. The data of this study was primary data, then analyzed with descriptive analysis. Results of data analysis showed that the average value of the validity handout with appear of the magazine was 84,64% and valid category. Result Analysis of the practicalities handout with appear of the magazine by teachers with Practical value was 83,26% with practicalities category, while by students the practical value was 83,95% with practicalities category. Concluded of the research was handout with appear of the magazine on the human respiratory system material for junior high school students produced a valid and practical criteria, so it can be used in the learning process.